Determinants of hypertension among adults living in Bole Sub-city, Addis Ababa - Selam Ayele Kassie; Kidanemariam G/Michael Beyene; Mesafint Abeje Tiruneh (International Journal of Public Health Science (IJPHS), 2020)
Complications of hypertension account for 9.4 million deaths world wide every year. Evidences indicated that hypertension and elevated blood pressure are increasing partly due to increase in determinants. In Addis Ababa, there is limited information on determinants of hypertension among adults. Hence, this study aimed to assess determinants of hypertension among adults living in Bole Sub-city, Addis Ababa. Community based unmatched case-control study was conducted. Simple random sampling technique was used to select 122 cases and 244 controls. Data were collected using interviewer administered structured questionnaire and measurement of blood pressure, weight and height. Binary logistic regression model was used for data analysis. A total of 348 adults were included in the study with 95% response rate. The study showed that age (AOR=7.68, 95% CI: 2.31–25.48), average family monthly in come (AOR=6.39, CI: 1.60-25.55), family history of hypertension (AOR=4.50, CI: 1.14-17.62), body mass index (AOR=3.76, CI: 1.49-9.48), physical activity (AOR=3.66, CI: 1.21–11.07), tobacco use (AOR=8.99,CI:2.02-39.86), salt consumption (AOR=5.22, CI: 1.47-18.48), stress (AOR=5.18, CI:2.42–11.09), knowledge (AOR=8.82, CI: 3.14-24.72) and diabetic mellitus (AOR=8.42, CI: 1.44-48.97) were significantly associated with hypertension. Cases had higher exposure to risk factors of hypertension than controls. Age, average family monthly income, physical activity, saltcon sumption, diabetic mellitus, stress, tobacco use, body mass index, family history of hypertension and knowledge were associated with hypertension. There is a need to health education to prevent tobacco use, regular exercise, reduce salt consumption and other life style modifications to reduce hypertension.